Penyelesaian Kepailitan Melalui Skema Restrukturisasi Utang Dalam Perspektif Omnibus Law (Kajian Terhadap Undang-Undang No. 6 Tahun 2023 Tentang Cipta Kerja) - Rizki; Nasution, Aisyah Artha Ramadhani (Legalita, 2025)
This research discusses the resolution of bankruptcy through a debt restructuring scheme from the perspective of the Omnibus Law, especially in Law No. 6 of 2023 concerning Job Creation. This change in regulations has a significant impact on the mechanism for settling debts for debtors who are experiencing financial difficulties. This study uses a juridical-normative method with a legislative approach and doctrinal analysis to examine the provisions of debt restructuring in the Job Creation Law and its implications for the bankruptcy system in Indonesia. The study also compares the mechanisms set out in previous regulations with the latest provisions to understand the effectiveness of the policies enshrined in the Omnibus Law. In addition, this study explores various challenges and opportunities faced in the implementation of debt restructuring schemes, including the role of commercial courts, creditors, and debtors in achieving fair and balanced solutions.